Generalized linear models a Bayesian perspective - Dey Dipak K; Ghosh Sujit K; Mallick Bani K (New York Marcel Dekker, 2000)
This volume provides a comprehensive overview of key statistical concepts and methodologies including the Bayesian approach for analysis of GLMs including logistic regression and log-linear models from both a theoretical and a practical point of view. In
Keywords: Bayesian statistical decision theory; Generalized linear models; Linear models(Statistics)